The use of e-groups (listserve mailing lists) for the development of the veterinary profession in Nigeria (2003)
The advent of the Internet hits opened diverse opportunities for sharing and exchange of information rapidly to a worldwide audience. One of such opportunities is the possibility of creating electronic mailing list (or e-group) containing several hundreds or even thousands of e-mail addresses. E-groups have the distinct advantage that a message need not he sent to the individual e-mail addresses hut to a single address and vet immediately gel posted to all members. The Yahoo ISP has some 180 e-groups on veterinary related topics including nigeriavetphpmforum, newly created by the author. The latter is aimed at promoting interactive veterinary public health and preventive medicine activities, information dissemination and education on relevant issues globally. The paper sheds some light on existing veterinary related e-groups, how to assess or join them and how to create new e-groups for the development of veterinary profession.